Research Development Trends in Project Based Learning (PjBL) Learning Models in Science Learning in Elementary Schools: Bibliometric Analysis - Muhamad Suhardi; Sholihah, Mar'atus; Rohmani (Universitas Pendidikan Ganesha, 2025)
Project Based Learning (PjBL) is a student-centered learning method, where learning is done through projects designed to answer questions or solve complex problems. The purpose of this study was to identify publications related to the Project Based Learning learning model in elementary school science learning in the last sixteen years (2008-2023) and visualize them. This study uses a descriptive bibliometric analysis method. The method of collecting data from the Scopus database through the stages of identification, screening, eligibility, and inclusion, where from 8,705 initial articles and 51 articles were selected. The data analysis method uses the publication frequency analysis method to see annual trends, keyword analysis to identify main topics, and data visualization in the form of simple graphs or maps to illustrate trends and relationships between topics. The results of the study show that studies related to PjBL (Project Based Learning) in elementary school science learning have been conducted in various countries, with the United States and Indonesia having the most publications. The research focus on themes such as